Activation of neuronal endothelin B receptors mediates pressor response through alpha‐1 adrenergic receptors. Issue 4 (20th February 2017) - Becker, Bryan K.; Speed, Joshua S.; Powell, Mackenzie; Pollock, David M.
Abstract: Abnormalities in activity of the endothelin (ET) system have been widely reported in a number of cardiovascular disease states such as hypertension and heart failure. Although the vascular responses to ET are well established, the interaction between ET and other important modulators of blood pressure, such as the sympathetic nervous system, are less understood. Previous reports implicate ET signaling through ET type B (ETB ) receptors in increasing neuronal activity. Therefore, we hypothesized that activation of ETB receptors on sympathetic nerves would increase blood pressure through an adrenergic‐mediated mechanism. Thus, we used anesthetized ETB ‐deficient rats, which only express functional ETB receptors on adrenergic neurons, and genetic controls, which express functional ETB receptors in vascular tissue and kidney epithelium. We determined the pressor response to the selective ETB receptor agonist sarafotoxin c (S6c). Separate groups of rats were treated with the α 1 ‐adrenergic receptor antagonist prazosin or the β ‐adrenergic receptor antagonist propranolol to elucidate the role of adrenergic signaling in mediating the blood pressure response. We observed a dose‐dependent pressor response to S6c in ETB ‐deficient rats that was reversed by prazosin treatment and augmented by propranolol. In genetic control rats, the effects of S6c on sympathetic neurons were mostly masked by the direct activity of ETB receptor activation on the vasculature. Heart rate was mostly unaffected by S6c across all groups and treatments. These results suggest that ETB activation on sympathetic neurons causes an increase in blood pressure mediated through α 1 ‐adrenergic receptor signaling. Abstract : Minute averages of changes in mean arterial blood pressure (MAP) in response to infusion of the endothelin type B (ETB ) receptor agonist, sarafotoxin c (S6c), in transgenic (TG) control (A) and ETB ‐deficient (B) rats treated with vehicle, prazosin, or propranolol. Because the ETB ‐def rats only have ETB receptors in nerves, these findings support the hypothesis that ETB receptors in nerves produce vasoconstriction through an alpha adrenergic receptor dependent pathway.